The gender gap in mental well-being during the Covid-19 outbreak: Evidence from the UK - Ben Etheridge; Lisa Spantig (University of Essex, Institute for Social and Economic Research (ISER), 2020)
We document a decline in mental well-being after the onset of the Covid-19 pandemic in the UK. This decline is twice as large for women as for men. We seek to explain this gender gap by exploring gender differences in: family and caring responsibilities; financial and work situation; social engagement; health situation, and health behaviours, including exercise. Differences in family and caring responsibilities play some role, but the bulk of the gap is explained by social factors. Women reported more close friends before the pandemic than men, and increased loneliness after the pandemic's onset. Other factors are similarly distributed across genders and so play little role. Finally, we document larger declines in well-being for the young, of both genders, than the old.
Keywords: I10; I14; I18; I30; 330; Mental well-being; Gender; Covid-19